Use Of Standard Clauses in Transactions Therapeutics Based on Regulation Theory - Carwan Carwan; Sari Indah Lestari (International Journal of Social Service and Research, 2023)
The standard informed consent clause is prepared and formed by one of the parties to make it easier for doctors and patients to create a therapeutic agreement. One of the parties designed and developed this standard clause to make it easier for doctors and patients to form a therapeutic contract. However, in practice, it is found that the application of standard clauses prepared in advance by hospitals or doctors is only concerned with signatures and has an impact of dissatisfaction that is detrimental to patients. The research method used is juridical-normative. The results showed that based on the theory of legislation, normatively, the standard clause does not violate the principle of freedom of contract because the standard informed consent clause in the Therapeutic Transaction is a form of the initiative of doctors and hospitals as parties who have more expertise to form the main guidelines for doctors and patients in carrying out health services. In Decision Number 63/Pdt.G/2021/PN Kpn, the use of standardized informed consent clauses in therapeutic agreements provides repressive legal protection in the trial and has a positive influence, namely strengthening informed consent as vital and valid evidence in the problem because it has guided whether medical actions are carried out by the agreed actions, SP, SOP, and patient needs.